BUDAYA NUSANTARA DALAM PERSPEKTIF PENGAJARAN DAN PENERAPAN HUKUM ISLAM - Fauziah, Ai Samrotul; Taufiqurrohman, Essa Salman; Hanafi, Hilmi; Kurniawan, Ilham (Ibn Khaldun University, Bogor, 2024)
The culture of Nusantara represents a wealth that reflects the diversity of ethnicities, traditions, and local values in Indonesia. From the perspective of Islamic law implementation, the interaction between local culture and Sharia norms is highly relevant. Islamic law, which is universal in nature, needs to be integrated with local cultures to ensure its acceptance and understanding by the community. This study employs a literature review method to analyze various primary and secondary sources, including Islamic legal texts, scholarly works, historical documents, and literature on Nusantara culture. It examines how the values of Nusantara culture, such as deliberation (musyawarah), mutual cooperation (gotong royong), and local wisdom, can strengthen the application of Islamic law within the social and cultural contexts of society. Through this approach, the study aims to highlight the importance of dialogue between Islamic law and local culture and its implications for fostering a harmonious and just society. The findings are expected to provide insights into the synergy between law and culture in creating a more effective and inclusive legal system in Indonesia.